UPAYA MENINGKATKAN HASIL BELAJAR IPS MELALUI PENGGUNAAN MEDIA GAMBAR PADA SISWA KELAS V DI SD NEGERI 001 PUJUD SELATAN KABUPATEN ROKAN HILIR - Elliya Nasution (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article focuses on how much improvement the learning outcomes in the field of social sciences learning obtained by students by using image or photo media are in the learning process about the geographical characteristics of Indonesia as an archipelagic or maritime and agrarian country in the odd semester of class V in the academic year of 2021/2022. The study provided in this article was conducted on the fifth-grade students at Public Elementary School 001 South Pujud in Rokan Hilir. The study involved 25 students of Class V, which consisted of 13 male and 12 female students. Data were collected through the observation by using observation sheets to determine the activity of teachers and students in the learning process that was implemented based on the Lesson Plan prepared by the researcher. And the data used to collect student learning outcomes were formative tests, which are carried out at the end of each cycle. According to the results of the study, using the picture use media could improve students’ learning outcomes in which before the improvement of learning the average value obtained by students on the test was 66.7. After the improvement, it was obtained 75 average scores in cycle I with 68% as the percentage of standard score achievement, and in cycle II, the average value was 78.4, with 88% as the percentage of standard score achievement. Students were easier to understand lessons and activities by using pictures so that students' abstraction power and learning outcomes increased.